Investor Perceptions of Financial Misconduct: The Heterogeneous Contamination of Bystander Firms - Paruchuri, Srikanth; Misangyi, Vilmos F. (Academy of Management Journal, 2015)
We suggest that, when one firm reveals financial misconduct, others in the industry suffer lower valuations, but do so heterogeneously. To understand this heterogeneity, we conceptualize such contamination as a generalization–instantiation process: investors generalize the culpability to the industry category and perceive the instantiation of generalized culpability within the industry bystander firms. This theoretical separation allows us to hypothesize the factors that affect the degree to which both of these elements of the contamination process occurs. Specifically, we predict that characteristics of the misconduct firm or event—factors that lend to investors' familiarity with the misconduct firms, or that prompt attributions of blame for the misconduct—affect the potency of the generalization of culpability to the industry, while characteristics of the industry bystander firms—investors' familiarity with such firms, or factors that lend to investors' perceptions that they have strong governance—affect the firms' vulnerability to being perceived as instantiating the generalized culpability. We tested our hypotheses on a sample of 725 firms across 84 financial misconduct events, and the results of our event analyses broadly support our predictions. Our study thus has implications for future research on the social view of financial markets, organizational misconduct, and corporate governance.